Context, Orders of Worth, and the Justification of Meat Consumption Practices. (12th October 2016) - Thorslund, Cecilie A. H.; Lassen, Jesper
Abstract: Although animal welfare is felt to be important by consumers, behavioural patterns do not fully reflect this. Rather than relating this attitude‐behaviour gap to hypocrisy, this article, building on pragmatic sociological theory and an empirical study, focuses on context‐dependent moral evaluations. An analysis of focus‐group interviews conducted in three countries shows that meat‐related consumption practices involve several competing sets of moral conventions, and the results demonstrate that public concerns about animal welfare vary depending on whether they relate to an everyday or production context. In the former, animal welfare does not play a big role, and given this it can be argued that people are not hypocritical, since the practices and perceptions are actually united within the given context. It is concluded that the lack of civic justifications in the context of everyday life calls for new ways of making animal welfare relevant in this context in order to support consumers in moving towards products with high standards of animal welfare.